2016
DOI: 10.1039/c6cc06517a
|View full text |Cite
|
Sign up to set email alerts
|

Single-step preparation of indium tin oxide nanocrystals dispersed in ionic liquids via oxidation of molten In–Sn alloys

Abstract: Oxidation of molten In-Sn alloys was carried out in ionic liquids by heat treatment with vigorous stirring, resulting in the formation of indium tin oxide (ITO) nanocrystals. The ITO nanocrystals exhibited a plasmon peak, the peak wavelength of which was blue-shifted with an increase in the Sn fraction in ITO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Likewise, their use as highperformance lubricants or lubricant additives 2 is similarly dependent on their remaining stable towards oxidation and high temperatures for extended periods, as will be their utility as additives (plasticizers, anti-static agents) to highperformance polymers, 3 and their suitability as solvents for high-temperature materials synthesis. 4 Yet, while ionic liquids have been widely touted as thermally stable, the unfortunate fact is that most are commonly unstable at high temperatures for extended periods of time. 5 Although short-term stability (minutes to perhaps hours) in the 200-300+ C range can be achieved, ILs which remain stable at such temperatures for days, weeks, or longer have proven elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, their use as highperformance lubricants or lubricant additives 2 is similarly dependent on their remaining stable towards oxidation and high temperatures for extended periods, as will be their utility as additives (plasticizers, anti-static agents) to highperformance polymers, 3 and their suitability as solvents for high-temperature materials synthesis. 4 Yet, while ionic liquids have been widely touted as thermally stable, the unfortunate fact is that most are commonly unstable at high temperatures for extended periods of time. 5 Although short-term stability (minutes to perhaps hours) in the 200-300+ C range can be achieved, ILs which remain stable at such temperatures for days, weeks, or longer have proven elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported previously that thermal oxidation of In metal in EMI-BF 4 at 523 K produced largely aggregated NPs but that similar heat treatment in HyEMI-BF 4 gave uniformly dispersed In 2 O 3 NPs of 28 nm in diameter, indicating that hydroxyl groups in cationic species of RTILs were strongly adsorbed on the metal oxide surface to improve the dispersibility of NPs in the solutions. 65 Thus, the results of the present study suggested that hydroxyl groups in HyEMI-BF 4 molecules could be adsorbed on the MoO x surface to retard the coalescence between NPs. The concentration of water in RTILs was also reported to signicantly affect the size of In 2 O 3 NPs formed, and the larger NPs were produced with an increase in the water concentration in RTILs.…”
Section: Preparation Of Molybdenum Oxide Nps Showing Lsprmentioning
confidence: 50%
“…The concentration of water in RTILs was also reported to signicantly affect the size of In 2 O 3 NPs formed, and the larger NPs were produced with an increase in the water concentration in RTILs. 65 In the present study, since the water concentration in HyEMI-BF 4 , 590 ppm, was much larger than that in EMI-BF 4 , 90 ppm, a higher growth rate of MoO x was expected in HyEMI-BF 4 , resulting in a larger number of NPs with a smaller average size. In both kinds of RTIL, the heated NPs were connected with each other to form a network structure.…”
Section: Preparation Of Molybdenum Oxide Nps Showing Lsprmentioning
confidence: 52%